Thai students’ intercultural apprehension in the Indonesian context - Fendy Yogha Pratama (Jurnal Bahasa Indonesia bagi Penutur Asing, 2021)
Intercultural apprehension can affect the adaptation process of BIPA learners while in Indonesia, but research on this topic is still very limited. This study aims to measure the level of intercultural anxiety and the factors that cause this type of anxiety in Thai students when communicating with Indonesian people who have cultural differences. The data collection was conducted using a questionnaire called PRICA (Personal Report of Intercultural Communication Apprehension) and interview guidelines. The results showed that 7.1% of students experienced high levels of intercultural apprehension, 64.2% of students experienced moderate levels of intercultural apprehension and 28.5% of students experienced low levels of intercultural apprehension. Language barriers, negative prejudice, and culture shock are the main factors that give rise to this anxiety. BIPA teachers and program organizers are expected to design learning activities that can involve Thai students and Indonesian students so that intercultural apprehension can be reduced.